Singing Positivity: Prosperity Gospel in the Musical Discourse of Popular Youth Hip-Hop Gospel in Zimbabwe - Gukurume, Simbarashe (Muziki, 2017)
Zimbabwe’s protracted anti-Euro-American imperialist rhetoric and subsequent draconian policies that imposed a 100 per cent local content on national radio and television birthed a particular type of popular urban youth music genre (urban grooves), which has radically transformed the urban public sphere in the country. In this article, I examine the music and lyrics of one prominent gospel urban grooves artist—Mudiwa “Hood” Mutandwa. I particularly analyse the complex intersections of his musical discourse with prosperity gospel dogma propagated in contemporary Pentecostal Charismatic Churches (PCCs). Mudiwa’s musical discourse resonates with prosperity gospel ideologies propagated in the emergent and popular PCCs in Zimbabwe. Mudiwa’s music not only creates, but also reinforces a consumerist and materialist culture amongst the urban youth in Harare. Although Mudiwa’s musical discourse runs counter to the grim economic realities on the ground, it enables the deprived urban youth to symbolically make sense of their nostalgic and yet elusive aspirations of being wealthy in an economic and political crisis symptomatic of a postcolonial state.
paid